2015
DOI: 10.1542/peds.2014-2560
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Replacement Therapy in Pregnancy and Major Congenital Anomalies in Offspring

Abstract: BACKGROUND AND OBJECTIVES: Nicotine replacement therapy (NRT) is now being used as a smoking cessation aid during pregnancy, although little is known about fetal safety. We assessed the relationship between early pregnancy exposure to NRT or smoking with major congenital anomalies (MCA) in offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…Furthermore, one conclusion (Kapur et al 2001) was based on a single case of rapid fetal movements in a subject given a placebo patch, while differences noted in the final study (Pollak et al 2007) were not significant. The only study reporting significantly worse outcomes in smokers using (or allocated to) NRT than in other smokers was the increased incidence of major respiratory system congenital abnormalities (Dhalwani et al 2015) and even here the authors noted “women prescribed NRT were considerably more likely to have diagnosed morbidities, particularly asthma and mental illnesses”. The remaining studies reported finding no effect, some for specific effects and some for a range of effects.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Furthermore, one conclusion (Kapur et al 2001) was based on a single case of rapid fetal movements in a subject given a placebo patch, while differences noted in the final study (Pollak et al 2007) were not significant. The only study reporting significantly worse outcomes in smokers using (or allocated to) NRT than in other smokers was the increased incidence of major respiratory system congenital abnormalities (Dhalwani et al 2015) and even here the authors noted “women prescribed NRT were considerably more likely to have diagnosed morbidities, particularly asthma and mental illnesses”. The remaining studies reported finding no effect, some for specific effects and some for a range of effects.…”
Section: Resultsmentioning
confidence: 87%
“…The RRs listed in Table 10 are based on comparison with smokers using NRT, this being non-significant 1.50 (0.94–2.41). A much larger UK study (Dhalwani et al 2015) only reported results for major congenital abnormalities, but found no association with overall risk. Combining the estimate for this study with those for any congenital abnormality in the other studies gave a random-effect estimate of 1.10 (0.86–1.41), which reduced to 1.02 (0.81–1.28) if the result for non-smokers from the Danish cohort was excluded.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…NRT is still rarely prescribed during pregnancy, due to concerns over fetal safety. One recent study found similar rates of major congenital anomalies for pregnant women prescribed NRT and those who continued to smoke (35% and 27%, respectively) (67). Findings must be interpreted with caution, however, as confounding factors such as intensity of smoking were not assessed.…”
Section: Pregnant Women: Special Considerationsmentioning
confidence: 98%